Négocier la reconnaissance de sa citoyenneté par le squat - Alizée Lazzarino (Genre, Sexualité et Société)
Based on a reflection on citizenship, this article analyzes the activist trajectory of a collective of female sex workers in Barcelona through their involvement in non-residential squats (illegally occupied spaces). A nine-month ethnographic study in squats in the Raval neighborhood frequented by neighbors and members of the collective Putas Indignadas showed how these women find in these illegal spaces the opportunity to express themselves, showcase their skills, and form alliances with local actors despite the criminalization of their presence in the city. The accessibility norms of the squats allow marginalized populations to create a public sphere in the absence of access to public space. Thus, the squats become places where it is possible to make “acts of citizenship.” In this way, they contribute to promoting the integration of sex workers into municipal decision-making processes regarding prostitution, from which they were initially excluded.